2017
DOI: 10.3390/nu9060576
|View full text |Cite
|
Sign up to set email alerts
|

Iron for Africa—Report of an Expert Workshop

Abstract: Scientific experts from nine countries gathered to share their views and experience around iron interventions in Africa. Inappropriate eating habits, infections and parasitism are responsible for significant prevalence of iron deficiency, but reliable and country-comparable prevalence estimates are lacking: improvements in biomarkers and cut-offs values adapted to context of use are needed. Benefits of iron interventions on growth and development are indisputable and outweigh risks, which exist in populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Chevon is a major source of micronutrients particularly, iron and potassium as well as vitamin B 12 . Iron deficiency results in anemia and this is a real threat to women of childbearing age, especially in rural areas [57,58]. The high concentration of iron (Fe) in chevon ( Table 5) makes it potentially a source of iron for pregnant women in rural areas where iron supplements may be difficult to access while high concentrations of potassium are essential for the maintenance of electrolyte and osmotic balance.…”
Section: Chevon: Acceptability Nutritional Value and Health Benefitsmentioning
confidence: 99%
“…Chevon is a major source of micronutrients particularly, iron and potassium as well as vitamin B 12 . Iron deficiency results in anemia and this is a real threat to women of childbearing age, especially in rural areas [57,58]. The high concentration of iron (Fe) in chevon ( Table 5) makes it potentially a source of iron for pregnant women in rural areas where iron supplements may be difficult to access while high concentrations of potassium are essential for the maintenance of electrolyte and osmotic balance.…”
Section: Chevon: Acceptability Nutritional Value and Health Benefitsmentioning
confidence: 99%
“…Around two thirds of the children at six month of age in our sample were anemic, early life interventions should be prioritize to reduce the likelihood of being anemic at that age. Improving overall household living conditions as well as increasing maternal education, delaying and spacing childbearing and introducing iron rich foods in weaning (33) could also have a positive impact on reducing anemia in infancy. Public health program should target infants from anemic mothers and infants in deprived households as they are at higher risk of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the results of the study conducted by Lozoff et al (2006) on 12 months old children resulted in 34.9% ID. The prevalence of iron deficiency was also very high in African countries, namely 51% in Algeria, 27% in Egypt, 51% in Ivory Coast , 21% in Kenya, 30% in Morocco and 11% in South Africa (Mwangi et al 2017). The results of the study by Chandyo et al (2016) in Bhaktapur, Nepal, revealed that the prevalence of iron deficiency is also very high, namely 17% in children aged ≤6 months and 30% in children aged 7-12 months.…”
Section: Iron Status In Undernourished Children Aged 6-23 Monthsmentioning
confidence: 96%